Fiscal Sustainability in Indonesia with Asymmetry - Mohamad Ikhsan; I Gede Sthitaprajna Virananda (Institute for Economic and Social Research, 2021)
The management of fiscal balance determines public debt sustainability, where a positive response of primary balance towards the debt ratio indicates a sustainable path. However, there might be asymmetry in the government’s fiscal management between different phases of the debt trajectory and business cycle. This study examines the sustainability of fiscal imbalance and public debt in Indonesia using the fiscal reaction function with annual fiscal data from 1976 to 2019. We incorporate asymmetry by decomposing the lagged debt ratio and cyclical output variables into their positive and negative partial sums. We find that Indonesia’s fiscal imbalance is on a path of weak sustainability as revenue grows more slowly than expenditure in the long run, with the bi-directional Granger causality between the two indicating fiscal synchronization. Long-run public debt sustainability is on a more sustainable path as primary surplus responds positively to the debt ratio. However, our asymmetric analysis suggests that this might be a false impression as primary balance decreases only in response to debt ratio decrease but increases less or fails to increase when the debt ratio rises, which is potentially dangerous.